Effect of Foliar Application of Plant Growth Regulators and Nutrients on Seed Yield and Quality Attributes of Mungbean (Vigna radiata (L) Wilczek - S.N. PATIL; R.B. PATIL; Y.B. SURYAWANSHI (Seed Research, 2026)
Studies were conducted to evaluate the effect of plant growth regulators and nutrients (urea) on seed yield and seed quality in mungbean (Vigna radiata (L) Wilezek. Among  different treatments, spraying of NAA (25ppm) recorded significantly higher seed yield by 21-22 per cent than control through increased flower production (18%), clusters per plant (24%), pod setting percentage (31%) and pods per plant (55%). The variety PM-9339 gave maximum seed yield, which was 11-12 per cent higher than Kop. 1. The higher seed yield was most probably due to more number of flowers per plant, pods/plant, seed yield/plant and 100-seed yield.